Comparative study of different methods of extracting bioactive compounds from wild edible plants (WEP) (Research, Society and Development, 2021)
Wild Edible Plants (WEP) are rustic species, cosmopolitan and normally easily adaptable to edaphoclimatic. They have one or more edible parts and are not normally included in our everyday diet. Most of these species can have different biological activities, mainly as antioxidants. The objective of this work was to evaluate the antioxidant capacity and quantify the main phenolic compounds of Leandra regnellii Cogn. (pixirica), Solanum americanum Mill (maria-pretinha) and Phytolaca thyrsiflora Hill. (fitolaca), in three different extraction methods, namely: 1) aqueous by reflux, 2) aqueous by maceration and 3) hydroethanolic. The highest antioxidant activity obtained was for L. regnellii, under hydroethanolic extract and under reflux. As for the content of phenolic compounds, the best results were obtained for the species L. regnellii in maceration extract, followed by P. thyrsiflora in extract using a reflux system. As for the quantification of major compounds by HPLC, the species L. regnellii also presented the highest content of phenolic compounds in the hydroethanolic extract, especially ferulic acid, gallic acid, naringin, epicatechin and hesperidin. In the species P. thyrsiflora, gallic acid and quercetin were identified in hydroethanolic extract and apigenin in maceration extract. S. americanum in the hydroethanolic extract, presented rutin, catechin, epicatechin and vitexin as main components. The present study shows expressive antioxidant activity as well as the presence of phenolic compounds that have biological activity, highlighting the importance of choosing the extraction method for future uses of these species by the food and pharmaceutical industry.